1998
DOI: 10.1096/fasebj.12.12.1101
|View full text |Cite
|
Sign up to set email alerts
|

BRE: a modulator of TNF‐α action

Abstract: A stress-responsive gene highly expressed in brain and reproductive organs (BRE) is down-regulated after UV irradiation, DNA damaging agents, or retinoic acid treatment. The human BRE gene encodes a mRNA of 1.9 kb, which gives rise to a protein of 383 amino acids with a molecular size of 44 kilodaltons. BRE is not homologous to any known gene and its function has not been defined. Here we report that BRE was identified multiple times in a yeast two-hybrid screen of a murine cerebellar cDNA library, using the j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 27 publications
3
43
0
Order By: Relevance
“…Cells receive external signals through surface death receptors, such as the widely expressed tumor necrosis factor receptor-1 and Fas (Nagata, 1997;Aggarwal, 2003), or internal stress signals such as DNA damage (Dive et al, 1992), to undergo the extrinsic or intrinsic pathway of apoptosis, respectively (Strasser et al, 1995). In a yeast two-hybrid experiment designed to isolate novel intracellular binding proteins of tumor necrosis factor receptor-1, brain and reproductive organ-expressed protein (BRE) was identified as one such protein that binds to the juxtamembrane domain of the death receptor (Gu et al, 1998). BRE was first discovered as a ultraviolet-responsive gene, whose transcription could also be downregulated by a DNA-damaging chemical, 4-nitroquinoline-1-oxide, and a differentiation-inducing agent, retinoic acid (Li et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Cells receive external signals through surface death receptors, such as the widely expressed tumor necrosis factor receptor-1 and Fas (Nagata, 1997;Aggarwal, 2003), or internal stress signals such as DNA damage (Dive et al, 1992), to undergo the extrinsic or intrinsic pathway of apoptosis, respectively (Strasser et al, 1995). In a yeast two-hybrid experiment designed to isolate novel intracellular binding proteins of tumor necrosis factor receptor-1, brain and reproductive organ-expressed protein (BRE) was identified as one such protein that binds to the juxtamembrane domain of the death receptor (Gu et al, 1998). BRE was first discovered as a ultraviolet-responsive gene, whose transcription could also be downregulated by a DNA-damaging chemical, 4-nitroquinoline-1-oxide, and a differentiation-inducing agent, retinoic acid (Li et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have also determined p53 expression was down-regulated; whereas TNF-R1 expression was up-regulated in SHEEC cells ( Figure 10). It has been reported that BRE can interact with the intracellular juxtamembrane domain TNF-R1 and inhibit the TNFinduced activation of NF-B (Gu et al, 1998). Therefore, we propose that BRE plays an antiapoptotic role in SHEEC cells.…”
Section: Comparative Proteomic Analysis Reveals Differentially Expresmentioning
confidence: 70%
“…Recent finding also showed that TRAF6 was involved in the RANK-TRAF6-NF-B pathways during osteoclastogenesis (Inoue et al, 2007). Overexpression of BRE in human 293 embryonic kidney cells has been reported to inhibit NF-B activation in response to TNF (Gu et al, 1998). This finding suggests that BRE indirectly cross-talk with TRAF6 and NF- , where it may play a central role in regulating cell proliferation, differentiation and survival.…”
Section: Protein Identification By Mass Fingerprintingmentioning
confidence: 93%
See 2 more Smart Citations